2020
DOI: 10.1007/s00406-020-01123-0
|View full text |Cite
|
Sign up to set email alerts
|

Differential neural processing of unpleasant sensory stimulation in patients with major depression

Abstract: An altered processing of negative salient stimuli has been suggested to play a central role in the pathophysiology of major depression (MD). Besides negative affective and social stimuli, physical pain as a subtype of negative sensory stimulation has been investigated in this context. However, the few neuroimaging studies on unpleasant sensory stimulation or pain processing in MD report heterogeneous findings. Here, we investigated 47 young females, 22 with MD and 25 healthy controls (HC) using fMRI (3.0 T). F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 37 publications
0
9
0
1
Order By: Relevance
“…All six analyses found significant associations between depression and pain, two of which sampled patients clinically diagnosed with major depressive disorder [ 45 , 46 ]. Malejko et al [ 45 ] was the only task-fMRI study that identified the primary somatosensory cortex (S1) as negatively correlated in depression with induced pain; participants reported severe clinically diagnosed depression, but pain severity was unknown.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All six analyses found significant associations between depression and pain, two of which sampled patients clinically diagnosed with major depressive disorder [ 45 , 46 ]. Malejko et al [ 45 ] was the only task-fMRI study that identified the primary somatosensory cortex (S1) as negatively correlated in depression with induced pain; participants reported severe clinically diagnosed depression, but pain severity was unknown.…”
Section: Resultsmentioning
confidence: 99%
“…All six analyses found significant associations between depression and pain, two of which sampled patients clinically diagnosed with major depressive disorder [ 45 , 46 ]. Malejko et al [ 45 ] was the only task-fMRI study that identified the primary somatosensory cortex (S1) as negatively correlated in depression with induced pain; participants reported severe clinically diagnosed depression, but pain severity was unknown. Berna et al (2010) and Strigo et al (2008) identified hippocampus/amygdala using task-fMRI in participants with moderate pain and minimal to clinically significant depression (greater activity in depression/pain than in healthy controls), after adjusting ratings of induced pain.…”
Section: Resultsmentioning
confidence: 99%
“…As part of a broader research project with different experiments of which findings are reported elsewhere [ 38 , 39 ], we investigated a total of 33 young adult female participants aged 18–38 years. Of those, 16 patients were diagnosed with MD whereas 17 healthy participants (HC) served as control group with no current or lifetime psychiatric diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The above shows that depression and pain are often co-morbid and decrease the quality of life of many individuals worldwide. An exact understanding of the pathophysiology of chronic pain and depression and of why comorbidity of these two disorders is so common is still a matter for research ( Thompson et al, 2016 ; Nitzan et al, 2019 ; Malejko et al, 2021 ). However, although the biological mechanisms are still to be explained, it has been hypothesised that depression and pain may share the same descending tracts of the central nervous system, possibly involving serotonin, noradrenaline, and dopamine ( Pinheiro Campos et al., 2020 ; Thompson et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%